2019
DOI: 10.7554/elife.46421
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging neuropeptide release at synapses with a genetically engineered reporter

Abstract: Research on neuropeptide function has advanced rapidly, yet there is still no spatio-temporally resolved method to measure the release of neuropeptides in vivo. Here we introduce Neuropeptide Release Reporters (NPRRs): novel genetically-encoded sensors with high temporal resolution and genetic specificity. Using the Drosophila larval neuromuscular junction (NMJ) as a model, we provide evidence that NPRRs recapitulate the trafficking and packaging of native neuropeptides, and report stimulation-evoked neuropept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…3G, H). This data is compatible with acute and rapid peptide release by partial LDCV fusion with the plasma membrane in the millisecond to second range, similarly to described kiss and run-type peptide release upon electrical stimulation (46,48).…”
Section: A Compartmentalized Network and Acute Ilp7 Release Transmit supporting
confidence: 85%
See 2 more Smart Citations
“…3G, H). This data is compatible with acute and rapid peptide release by partial LDCV fusion with the plasma membrane in the millisecond to second range, similarly to described kiss and run-type peptide release upon electrical stimulation (46,48).…”
Section: A Compartmentalized Network and Acute Ilp7 Release Transmit supporting
confidence: 85%
“…Descriptions of acute signaling function in sensory behavior however are rare. Acute neuropeptide release has been detected upon electrical stimulation of Drosophila motoneurons (20,46), and Substance P is released from primary nociceptors in mice and required for high stimulus pain responses (65,66). Here, we showed that Ilp7 is acutely released from Dp7 neurons in response to noxious light and acts on downstream ABLK neurons, presumably via its cognate receptor Lgr4 to enable photonociceptive responses and behavior.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Super-resolution 3D immunohistologies like array tomography (Smith, 2018) and 3D single-molecule methods (Jia et al, 2014; von Diezmann et al, 2017) will enable imaging of dense-core vesicle localization and neuropeptide contents in type-specific network anatomical context. Genetically encoded fluorescent dense-core vesicle cargos will allow real-time detection of neuropeptide secretion (Ding et al, 2019), while genetically encoded sensors of extracellular GPCR ligands (Patriarchi et al, 2018; Sun et al, 2018), GPCR activation (Haider et al, 2019; Hill and Watson, 2018; Livingston et al, 2018; Ratnayake et al, 2017; Stoeber et al, 2018), G-protein mobilization (Ratnayake et al, 2017), cAMP concentration (Hackley et al, 2018; Ma et al, 2018), protein kinase activation (Chen et al, 2014) and protein phosphorylation (Haider et al, 2019) will enable fine dissection of NP dynamics and NP-GPCR signal transduction events (Spangler and Bruchas, 2017). In addition, new caged NP-GPCR ligands (Banghart et al, 2018) and antagonists (Banghart et al, 2013) will provide for precise spatial and temporal control for NP receptor activation.…”
Section: Discussionmentioning
confidence: 99%
“…Use of the S-slope does require simplifications that occur with both PBP-based and GPCR-based fluorescent biosensors. These simplifications may not occur with less direct sensors such as those that measure Ca fluxes (Ding et al, 2019) or gene activation (Bick et al, 2017). One simplification appropriate to both PBP-based and GPCR-based biosensors: the Hill slope is near unity, so that responses < the EC 50 remain linear with the [drug].…”
Section: Discussionmentioning
confidence: 99%